Relationship between Functional Movement Screen Tests with Static and Dynamic Balances in Male Adolescent Volleyball Players of Golestan Province - Arazzadeh, Hamed; Norasteh, Ali Asghar (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Functional movement screen test is a valid test for evaluation of functional impairment and diagnosis of asymmetric motor patterns. The aim of this study was to investigate the relationship between (FMS) test and static and dynamic balances in adolescent volleyball players. Materials and Methods: This study was a correlational research which involved 30 male volleyball players in the Golestan Province League. The FMS tests include: (shoulder mobility, straight leg raise, Trunk Balance Push-Up, Rotary Balance, In-Line Lunge, Deep Squat, Hurdle Step). As a measurement tool for sport injury prevention and to evaluate static and dynamic balances, the Stork stand and Y balance test were used. Results: The results showed that there was a significant relationship between FMS test and dynamic balance (R2=36.24, R=0.602, P=0.001) and static balance (R2=19.62, R=0.443, P=0.001). Conclusion: Given the moderate relationship between variables, other performance tests such as balance tests to prevent sports injury and the athlete's return to exercise after the injury have been introduced. Selecting the appropriate test for athletes to prevent injuries by coaches and sports professionals are required and can be effective in reducing the cost of treatment and increasing exercise levels. Keywords: Dynamic Balance, Functional Movement Screening, Static Balance, Volleyball